Do good things really come to those who wait? An analysis of the average time of acceptance in Brazilian surgery journals - Lívia Guerreiro de Barros Bentes; Maria Fernanda de Almeida Cavalcante Aranha; Mariana Kondo Obara; Larissa Yoshie Shibata; Pablo Rodrigues Nunes de Souza; José Felipe Teixeira Borges; Leonardo Barbosa Duarte; Luiz Felipe Silva Marcião; Rui Sérgio Monteiro de Barros (Acta Cirúrgica Brasileira, 2024)
ABSTRACT Purpose: To analyze the average time between submission and acceptance of national journals in seven Brazilian surgery journals from 2017 to 2022. Methods: It consists of a cross-sectional and observational study with a quantitative approach to analyze the acceptance time of articles approved by Brazilian journals on general surgery and its subspecialties, including Acta Cirúrgica Brasileira, Jornal Vascular Brasileiro, Arquivos Brasileiros de Cirurgia de Digestiva, Revista do Colégio Brasileiro de Cirurgiões, Journal of Coloproctology, Revista Brasileira de Cirurgia Plástica, and International Brazilian Journal of Urology. Results: The journals with the lowest average waiting times were Revista do Colégio Brasileiro de Cirurgiões, Acta Cirúrgica Brasileira, and Journal of Coloproctology, respectively, and, with the lowest interquartile range there is Acta Cirúrgica Brasileira. There was no significant difference between the pre-pandemic and pandemic periods. The study designs with the highest and lowest means were, respectively, ideas and innovations – also with the highest interquartile range – and expert opinion, while with the lowest interquartile range was technical skill. Conclusions: The acceptance time for articles in Brazilian surgery journals is extremely variable. Identifying these discrepancies highlights the importance of understanding editorial processes and seeking ways to improve consistency and efficiency in reviewing articles.